The Influence of Financial Literacy, Financial Technology, Financial Attitude, Financial Skills, and Financial Behavior of Generation Z on Financial Inclusion of Islamic Banking in E-Commerce Transactions - Azafii, Azka Saputra; Tubastuvi, Naelati; Rahmawati, Ika Yustina; Widyaningtyas, Dian (International Journal of Business and Applied Economics, 2025)
This research aims to examine the influence of financial literacy, financial technology, financial attitudes, financial skills, and financial behavior of the Banyumas Generation Z community on financial inclusion among Sharia banking customers. The sample used was 120 respondents using an incidental sampling technique. This research applies quantitative methods to evaluate the relevance of each variable. The data collection instrument was carried out using a five-level Likert scale questionnaire. The analysis tool uses SEM PLS. According to the findings of this research, financial literacy, financial technology, financial attitudes, financial skills and financial behavior have a positive influence on financial inclusion.